Perancangan Virtual Private Network Point to Point Berbasis Mikrotik - Hidayatulloh, Syarif; Rahmawati, Eva (LPPM STMIK ANTAR BANGSA, 2018)
AbstractÃ¢â‚¬â€ Today, the internet is the most popular medium for communicating. Its benefits are very much for everyday life. One of the benefits is to exchange data in job activities. Currently the Ministry of Agriculture uses the internet to send data to headquarters. The Ministry of Agriculture has several office locations centered in Ragunan. Data exchange activities currently still use the services of e-mail sites that have limitations of the sites of the provider of the extreme letters. Application of VPN can increase security and the effectiveness of data or information exchange activities. This research is to design VPN at Ministry of Agriculture office safe and fast in conducting process of sending data from and to head office. The design of VPN office of the Ministry of Agriculture uses Virtual software with Mikrotik server. The result of the VPN can help the performance of employees of the Ministry of Agriculture to exchange data and information to and from the headquarters. IntisariÃ¢â‚¬â€ Saat ini, internet adalah media yang paling populer untuk berkomunikasi. Manfaat nya sangat banyak bagi kehidupan sehari-hari. Salah satu manfaatnya adalah untuk bertukar data dalam aktifitas pekerjaan. Saat ini Kementrian Pertanian menggunakan internet untuk mengirimkan suatu data ke kantor pusat. Kementrian pertanian memiliki beberapa lokasi kantor yang terpusat di Ragunan. Aktifitas bertukar data saat ini masih menggunakan jasa situs-situs penyedian surat elektronik yang memiliki keterbatas-keterbatas dari situs-situs penyedia surat ektronik tersebut. Penerapan VPN dapat meningkatkan keamanan dan efektifas dari kegiatan bertukar data atau informasi. Penelitian ini adalah untuk merancang VPN pada kantor Kementrian Pertanian yang aman dan cepat dalam melakukan proses pengiriman data-data dari dan ke kantor pusat. Perancangan VPN kantor Kementrian Pertanian mengunakan software Virtual dengan server Mikrotik. Hasilnya VPN dapat membantu kinerja pegawai Kementrian Pertanian bertukar data dan informasi dari dan ke kantor pusat. Kata KunciÃ¢â‚¬â€ Internet, Mikrotik, Virtual Private Network